LITERATURE REVIEW: GAMBARAN PEMERIKSAAN TES WIDAL DENGANPEMERIKSAAN PERTUMBUHAN KULTUR BAK-TERI SALMONELLA TYPHI PADA PASIEN DEMAM TIFOID ANAK - Sandi Paufik; Noor Muthmainah; Rahmiati Rahmiati; Dewi Indah Noviana Pratiwi; Lisda Hayatie (Homeostasis, 2022)
Typhoid fever is a systemic contamination because of Salmonella typhi micro organism, with unfold via the fecal-oral route. Currently, the diagnosis of typhoid fever in Indonesia remains broadly utilized by the Widal take a look at method. From a few data, the sensitivity and specificity values of the Widal take a look at aren't as accurate because the Tubex ™ take a look at. Therefore, this has a look at will investigate a literature assessment that examines the assessment of the Widal take a look at with blood culture in pediatric typhoid fever patients. The layout of this studies is a literature review. Search for posted articles on google schoolar the usage of decided on keywords, namely: evaluate of the Widal take a look at with exam of the boom of Salmonella typhi microorganism in kids with typhoid fever. Based at the assessment results, the av-erage fee of sensitivity is 69.5%, specificity is 67.9%, fantastic predictive fee is 37.9% and poor predictive fee is 86.0%. Widal's exam of the 11 calculated journals has a low common PPV fee and an excessive common NPV fee. Sensitivity and Specificity values are within side the variety of 60%. Conclusion primarily based totally on evaluations from sev-eral journals, the Widal take a look at can not be used to verify a prognosis however to rule out the opportunity of a diagnosis of different diseases